Ghana : 2013 Article IV Consultation. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2013)
This 2013 Article IV Consultation highlights that economic growth in Ghana continued at a robust pace of 8 percent in 2012 amid rising fiscal and external imbalances. Fiscal pressures came to the fore in a mounting public sector wage bill and costly energy subsidies that pushed the deficit close to 12 percent of GDP. The growth momentum continues into 2013, with increased oil production projected to keep overall GDP growth close to 8 percent. Non-oil growth is likely to decelerate, however, as a result of energy disruptions and high real interest rates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet